2020
DOI: 10.3390/cells9051270
|View full text |Cite
|
Sign up to set email alerts
|

Activated Cardiac Fibroblasts Control Contraction of Human Fibrotic Cardiac Microtissues by a β-Adrenoreceptor-Dependent Mechanism

Abstract: Cardiac fibrosis represents a serious clinical problem. Development of novel treatment strategies is currently restricted by the lack of the relevant experimental models in a human genetic context. In this study, we fabricated self-aggregating, scaffold-free, 3D cardiac microtissues using human inducible pluripotent stem cell (iPSC)-derived cardiomyocytes and human cardiac fibroblasts. Fibrotic condition was obtained by treatment of cardiac microtissues with profibrotic cytokine transforming growth factor β1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…However, after TGFβ1 stimulation and differentiation of fibroblasts toward myofibroblasts, fibroblast‐specific depolarization or hyperpolarization directly modulated cardiomyocyte membrane potential and accelerated or blocked spontaneous beating, respectively. Together, multiple studies have demonstrated the role of electrical coupling of activated myofibroblasts and cardiomyocyte in aging and disease [98], but the extent of cardiac fibroblast–cardiomyocyte interactions in the healthy heart and the role they play in the maintenance of electrophysiological conduction remains to be elucidated.…”
Section: Communication Between Fibroblasts and Cardiomyocytesmentioning
confidence: 99%
“…However, after TGFβ1 stimulation and differentiation of fibroblasts toward myofibroblasts, fibroblast‐specific depolarization or hyperpolarization directly modulated cardiomyocyte membrane potential and accelerated or blocked spontaneous beating, respectively. Together, multiple studies have demonstrated the role of electrical coupling of activated myofibroblasts and cardiomyocyte in aging and disease [98], but the extent of cardiac fibroblast–cardiomyocyte interactions in the healthy heart and the role they play in the maintenance of electrophysiological conduction remains to be elucidated.…”
Section: Communication Between Fibroblasts and Cardiomyocytesmentioning
confidence: 99%
“…This Special Issue includes articles highlighting the effective use of induced pluripotent stem cells (iPSCs) to develop cardiac microtissue [ 1 ], neurospheres [ 2 ], and cortical progenitors [ 3 ]. In addition, this Special Issue contains work on scaffolds with mesenchymal stem cells (MSCs) [ 4 ] and embryonic stem cells (ESCs) [ 5 ].…”
mentioning
confidence: 99%
“…A very relevant problem in cardiology is cardiac fibrosis. In the work by Blyszczuk et al, a model of fibrotic cardiac microtissue was generated using iPSC-derived cardiomyocytes and cardiac fibroblasts by treatment with transforming growth factor β1 (TGF- β1) or by use of cardiac fibroblasts from heart failure patients [ 1 ]. The authors demonstrated that activated cardiac fibroblasts could, via direct stimulation of β-adrenoreceptor signaling, promote cardiac contraction rate.…”
mentioning
confidence: 99%
See 2 more Smart Citations